Penerapan Model Pembelajaran Kooperatif Think Talk Write Untuk Meningkatkan Komunikasi Matematis Siswa MAN 1 Medan - Semi Syaina Amanda; Asrin Lubis (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2024)
This research aims to enhance the mathematical communication skills of students after implementing the Think Talk Write cooperative learning model. The study was conducted in the first semester of the 2023/2024 academic year in class XI MIA 3 at MAN 1 Medan. The subjects of this research were 39 students from class XI MIA 3 MAN 1 Medan. The object of this research was the mathematical communication skills of students by applying the Think Talk Write learning model. The research method used was classroom action research conducted over 2 cycles. The results of the students' mathematical communication skills test showed improvement from the initial test to the tests given in Cycle I and Cycle II. In the initial test, only 1 student (2.5%) achieved proficiency with an average score of 56, categorized as low. In Cycle I, there was a classical increase, with 10 students (25.6%) achieving proficiency with an average score of 67.9, categorized as moderate. In Cycle II, there was also a classical increase, with 33 students (84.6%) achieving proficiency with an average score of 86.9, categorized as high. It can be concluded that by implementing the Think Talk Write cooperative learning model, it is possible to improve the mathematical communication skills of class XI MIA 3 students at MAN 1 Medan.